ANALYSIS OF ECONOMIC INDICATORS IN IMPROVING THE TRADE BALANCE IN INDONESIA FOR THE PERIOD 2013-2023 - Nababan, Jeniwati; Wahyu Indah Sari; Nasution, Lia Nazliana (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
This study aims to analyze the monetary indicator variables on the stability of goods and services prices before and during the Covid-19 pandemic. The data used are secondary data obtained from the publications of the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). The analytical method employed is the Error Correction Model (ECM) to examine the short-term and long-term relationships between monetary variables (money supply, interest rate, exchange rate, and inflation) and price stability. The results indicate that before the Covid-19 pandemic, the variables of money supply and exchange rate had a significant effect on price stability, while the interest rate had no significant effect. Meanwhile, during the Covid-19 pandemic, the interest rate and inflation significantly affected price stability, whereas the money supply and exchange rate were not significant. These findings suggest that monetary dynamics before and during the Covid-19 pandemic differed in their influence on the stability of goods and services prices.